2009
DOI: 10.1080/00071660902873947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding metabolite combinations produced byLactobacillus plantarumon growth performance, faecal microbial population, small intestine villus height and faecal volatile fatty acids in broilers

Abstract: 1. Four combinations of metabolites produced from strains of Lactobacillus plantarum were used to study the performance of broiler chickens. 2. A total of 432 male Ross broilers were raised from one-day-old to 42 d of age in deep litter pens (12 birds/pen). These birds were divided into 6 groups and fed on different diets: (i) standard maize-soybean-based diet (negative control); (ii) standard maize-soybean-based diet + Neomycin and Oxytetracycline (positive control); (iii) standard maize-soybean-based diet + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 33 publications
8
80
0
6
Order By: Relevance
“…The finding could be due to the presence of organic acids such as lactate and acetate in the metabolite which act as an acidifying agent [14]. Previous research had reported similar finding when Lactobacillus metabolite was added into diet of broilers [12,21] and pigs [13]. …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The finding could be due to the presence of organic acids such as lactate and acetate in the metabolite which act as an acidifying agent [14]. Previous research had reported similar finding when Lactobacillus metabolite was added into diet of broilers [12,21] and pigs [13]. …”
Section: Discussionmentioning
confidence: 80%
“…The determination was done using GLC method as described by Thanh et al [21]. One gram of faeces was added into a rest tube containing one mL of 24% (v/v) metaphosphoric acid which was diluted in sulfuric acid 3 N. The acidic mixture was left at room temperature for overnight and centrifuged at 10 000 G for 20 min at four °C.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with Lee et al (2009), who explained that cholesterol reduction by LAB may involve five mechanisms: (i) LAB inhibit cholesterol synthesis enzymes and thus reduce cholesterol production; (ii) LAB facilitate the elimination of cholesterol in faeces; (iii) LAB inhibit the absorption of cholesterol back into the body by binding with cholesterol; (iv) LAB interfere with the recycling and enhancing the excretion of bile salts; (v) due to the assimilation of lactic acid. Thanh et al (2009) also reported that feeding of metabolite combinations produced by Lactobacillus plantarum had lower plasma triacylglycerol and cholesterol ester in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Foo et al (2003) also reported that Lactobacillus cultures from fermented products decreased plasma cholesterol concentration in rats. Recently, metabolites of LAB containing lactic, acetic, propionic, butyric acids, ethanol and bacteriocins were able to increase faecal LAB, volatile fatty acids and decrease faecal pH, plasma cholesterol in rats and chickens (Foo et al, 2005;Thanh et al, 2009). Moreover, Loh et al (2009) reported that feeding of spray-dried metabolites from L. plantarum reduced plasma cholesterol and increased essential fatty acids in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Several L. plantarum strains that isolated from Malaysian foods have been demonstrated to play an important role in maintaining the overall health of rats and livestock (Loh et al, 2008Thanh et al, 2009;Choe et al, 2012;Thu et al, 2011a). They were able to enhance overall growth performance, gut health, preventing or reducing the diarrhoea incidents and improve the general immune system.…”
Section: Introductionmentioning
confidence: 99%